Denosumab-induced hypocalcaemia in metastatic castrate-resistant prostate cancer. (12th December 2019) - Gunawan, Florence; George, Elizabeth; Kotowicz, Mark
Abstract : Summary: Denosumab is a fully human MAB that acts as a potent anti-resorptive by inhibiting activation of osteoclasts by inhibiting the receptor activator of nuclear factor-kappa B (RANK) ligand. Hypocalcaemia has been reported as one of the serious adverse sequelae of use of denosumab. We present a case of refractory hypocalcaemia following administration of a single dose of denosumab in a patient with metastatic castrate-resistant prostate cancer. The patient's serum calcium and vitamin D concentrations and renal function were normal prior to denosumab administration. Serum alkaline phosphatase (ALP) level was however elevated pre-morbidly consistent with known bone metastases. The patient was treated with high-dose oral and IV calcium without any appreciable response in serum calcium. During his 30-day hospital admission, he demonstrated disease progression with development of new liver metastases and bone marrow involvement. Normocalcaemia was not achieved despite 1 month of aggressive therapy. Given the patient was asymptomatic and prognosis guarded, he was eventually discharged for ongoing supportive care under the palliative care team. Learning points: Denosumab is a potent anti-resorptive therapy and hypocalcaemia is one of the known adverse effects. Serum calcium and vitamin D concentrations must be replete prior to administration of denosumab to reduce the risk of hypocalcaemia. Denosumab has been proven to be more effective than zoledronic acid in preventing skeletal-related adverse effects in patients with metastatic castrate-resistant prostate cancer.